2016
DOI: 10.1128/genomea.01447-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Whole-Genome Sequence of the Alkaliphilic Alishewanella aestuarii Strain HH-ZS, Isolated from Historical Lime Kiln Waste-Contaminated Soil

Abstract: Here, we present the whole-genome sequence of an environmental Gram-negative Alishewanella aestuarii strain (HH-ZS), isolated from the hyperalkaline contaminated soil of a historical lime kiln in Buxton, United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Of the environmental taxa, the identified genera include Alishewanella , Aminivibrio , Bacillus , Cloacibacterium , Okibacterium , Paenibacillus , Pseudomonas , and Streptococcus . Alishewanella , a member of the core microbiome, was identified in all 10 pine nut brands at proportional abundances of 0.6–5.3%, with the greatest abundances observed in brands H and I. Alishewanella is a relatively new bacterial taxon and since its discovery in 1992 has been isolated from water and landfill soil [ 25 , 26 ]. Alishewanella is thought to play a role in the bioremediation process of chromate and sulfate [ 25 ] which provides insight into its existence in landfill and waste soil.…”
Section: Resultsmentioning
confidence: 99%
“…Of the environmental taxa, the identified genera include Alishewanella , Aminivibrio , Bacillus , Cloacibacterium , Okibacterium , Paenibacillus , Pseudomonas , and Streptococcus . Alishewanella , a member of the core microbiome, was identified in all 10 pine nut brands at proportional abundances of 0.6–5.3%, with the greatest abundances observed in brands H and I. Alishewanella is a relatively new bacterial taxon and since its discovery in 1992 has been isolated from water and landfill soil [ 25 , 26 ]. Alishewanella is thought to play a role in the bioremediation process of chromate and sulfate [ 25 ] which provides insight into its existence in landfill and waste soil.…”
Section: Resultsmentioning
confidence: 99%
“…6 and 7). Some of the microbial phyla (Cyanobacteria, Chloroflexi, Chlamydiae and Euryarchaeota) indigenous to deep subsurface environments (Puente-Sánchez et al, 2014, 2018Fullerton and Moyer, 2016;Rempfert et al, 2017) were only observed in the core OTUs of lower depths (DF4 onwards). The microbial families (Carnobacteriaceae, Rhodobacteraceae, Clostridiaceae 1, Cellulomonadaceae, Erysipelotrichaceae, Cyclobacteriaceae, Opitutaceae, Bradyrhizobiaceae and Desulfovibrionaceae) detected in the core OTUs of DF were different from the microbial families (Idiomarinaceae, Moraxellaceae, Methylophilaceae, Nocardioidaceae, Nitrosomonadaceae, Enterobacteriaceae, Comamonadaceae, Chitinophagaceae) detected in granitic core OTUs at higher depths (1500 m b.s.)…”
Section: Discussionmentioning
confidence: 99%
“…The sequence reads obtained were submitted to the sequence read archive (SRA) under SRA accession: SRP155468. It can be accessed from the following link: https: //www.ncbi.nlm.nih.gov/bioproject/PRJNA482760/ (Sar, 2018).…”
mentioning
confidence: 99%